Metal contamination in sediments of River Kalu, Maharashtra, India: Insights from pollution indices, health risk evaluation, and multivariate methods - Sayli Salgaonkar; Akshay Botle; Rahul Tiwari; Gayatri Barabde (Sustainable Chemistry for Climate Action, 2025)
The metal pollution of sediments of Kalu River in Maharashtra, India, was analyzed using pollution indices and multivariate methods, with health risk evaluation to gauge the carcinogenic and noncarcinogenic effects of metals on human population. Eighty-four sediment samples from seven different locations along the flow path of the river were collected for a year ranging from February 2023 to January 2024 and analyzed using inductively coupled-plasma optical emission spectrophotometer. The metal mean concentrations were as follows (in mg/kg): Fe, 70416.416; Zn, 187.229; Mn, 717.430; Cu, 36.724; Cr, 109.074; Cd, 0.332; Ni, 76.317; Pb, 5.244; Se, 0.292; As, 0.229; and Hg, 0.258. The metal results of sediments on comparison with Sediment Quality Guidelines (SQGs) showed the following results: concentrations of Cd, Pb, and As were low; however, Cr and Ni were slightly more than the guideline values. On evaluating using pollution indices, it was found that river was slightly polluted at few sites owing to the anthropogenic activities carried out along the length of the river. Multivariate analysis showed mixed sources of metal pollution, namely, natural and human-induced activities. The health risk was found to be greater for children than adults via ingestion route; however, harmful effects were posed by Fe according to the hazard quotient. Tolerable carcinogenic risk was seen in adults and children on assessing the cancer index for Cr, Ni, and Cd. Overall study indicates that Kalu river is not heavily contaminated, but could become worse if the same pollution trend continues in the future.